Polar Mesospheric Winter Echoes - an analysis of selected cases - Ettestad, Kristine (UiT Norges arktiske universitet, 2022)
Polar Mesospheric Winter Echoes (PMWE) are strong coherent radar echoes, from the upper mesosphere at 55-85 km that are observed typically from end of August until beginning of May. Some models to explain PMWE formation suggest that they form because of turbulence in the atmosphere. Other models suggest that the PMWEs form like summer polar mesospheric echoes (PMSE) where charged dust particles must be present in addition to the turbulence. To examine the validity of the models, this work considered the PMWE detections made between 2008 and 2020 with the EISCAT VHF 224 MHz radar. PMWE were found in 11 datasets. Analyses of the PMWE spectra showed that they are better described with a Gauss profile rather than a Lorentz profile; the amplitudes, widths and frequency shifts of the spectra were derived and presented as function of time and altitude. These values were not vastly different from those of the PMSE that was considered for comparison. In 8 of the PMWE observations, the EISCAT heater was also operated; the heater emits HF radio waves that instantaneously raise the electron temperature at the altitude where the radio wave is attenuated. It was found that PMWE observed without heating had a larger overall spectral width than those observed with heating. The heater is operated in on-off modes, and it was noted that two of the PMWE observations during heating showed signal overshoot when the heater was turned off again. Such overshoots are commonly observed in PMSE and attributed to the effects of charged dust. The author concludes that the overshoot observation indicates that these two PMWEs most likely also form in the presence of charged dust. For the other PMWE observations it is unclear whether the pure turbulence assumption or the dust turbulence model applies. Python codes were written for data evaluation, which can be found in the appendix of the work.